A prospective investigation of the impact of smoking bans on tobacco cessation and relapse. Issue 3 (1st September 2001) - Longo, Daniel R; Johnson, Jane C; Kruse, Robin L; Brownson, Ross C; Hewett, John E
Abstract : BACKGROUND AND OBJECTIVES: To examine the long term impact of workplace smoking bans on employee smoking cessation and relapse. Over three years we studied a total of 1033 current or former smokers (intervention group) employed in smoke-free hospitals and 816 current or former smokers (comparison group) employed in non-smoke-free workplaces. The design of this natural experiment is a prospective cohort study. We randomly selected both hospitals and employees from 12 strata based on hospital size and state tobacco regulations, and sampled employees in the same communities. Main outcome measures were post-ban quit ratio and relapse rate. RESEARCH DESIGN: Between groups comparisons were conducted using the Cochran-Mantel-Haenszel statistic for general association, stratified Cox proportional hazards models, and the CMH analysis of variance statistic based on ranks. McNemar's test and the sign test were used to test for changes over time within each group. RESULTS: Differences in the post-ban quit ratio were observed between intervention and comparison groups (p ⩽ 0.02). For employees whose bans were implemented at least seven years before survey, the post-ban quit ratio was estimated at 0.256, compared with 0.142 for employees in non-smoke-free workplaces (p = 0.02). After controlling for a variety of factors, time to quit smoking was shorter for the hospital employees (p < 0.001), with an overall relative risk of quitting of 2.3. Contrary to expectations, relapse rates were similar between the groups. CONCLUSION: Employees in workplaces with smoking bans have higher rates of smoking cessation than employees where smoking is permitted, but relapse is similar between these two groups of employees. The results of this investigation have international applicability for policy makers, clinicians, employers, and employees. Countries should review smoking policies in workplaces in light of their own smoking patterns and efforts to deal with environmental tobacco smoke.